Mechanisms of highly stabilized ex-situ oleic acid-modified iron oxide nanoparticles functionalized with 4-pentynoic acid - Baharuddin, Aainaa Aqilah; Ang, Bee Chin; Abu Hussein, Nurul Athirah; Andriyana, Andri; Wong, Yew Hoong (Elsevier, 2018)
In this paper, the main objective is to successfully functionalize 4-pentynoic acid on iron oxide nanoparticles (NPs) which arises second objective; to ex-situ modify different concentrations of oleic acid on the NPs. A new understanding has been achieved as to how the concentrations of oleic acid prior ex-situ modification, play a major role in the successful functionalization of 4-pentynoic acid on the NPs. The functionalization proposed is a potential alternative route of creating an acid anhydride from two carboxylic acids without the use of dehydrating agent. Unmodified NPs were synthesized by co-precipitation method and were altered to pH 12 using NH4OH to promote dispersity right before ex-situ modification with oleic acid (0.2–0.8 wt % oleic acid to iron oxide) and subsequent 4-pentynoic acid (1.63 × 10−3 mol) functionalization. Characterizations were conducted by X-ray-diffraction (XRD), Transmission Electron Microscopy (TEM), Thermogravimetric and Differential Thermal analysis (TGA-DTA), Fourier transform infrared spectroscopy (FTIR), proton nucleic magnetic resonance (NMR) and Zetasizer. A monolayer oleic acid is produced for ex-situ modification of 0.2 wt % oleic acid to iron oxide. Whereas the higher concentrations of oleic acid ex-situ modifications generate bilayer oleic acid-modified iron oxide NPs to which, functionalization of 4-pentynoic acid is only successfully performed. The samples pose highly stabilized dispersions at pH 12 varying between -42 and -75 mV, whereas the mean hydrodynamic particle size distributions are achieved at approximately 35–48 nm. Mechanisms of ex-situ modifications of different oleic acid concentrations and functionalization of 4-pentynoic acid on the iron oxide NPs at pH 12 and 333.15 K are also proposed.